Subjectivity of Machines in Judicial Decision-Making - Montañez Sierra, Cristian Fernando (2021)
The questioning of the subjectivity of the legal agent who, executing their work and based on judicial discretion, prints particular aspects such as emotions, typical of the human essence in the sentence, is the central theme of this article. With the implementation of new actors such as digital judges, these aspects acquire a relevant role for those who are now in charge of deliberating. The objective of the article is to evaluate the role of subjectivity, initially from the role of judges, to later involve artificial intelligence programmers who assist tasks in making judicial decisions. What about the subjectivity that would no longer directly permeate the one in charge of judging? In other words, the empathy that the judicial agent currently generates finds new allies with whom they work together. The analysis is based on articles that deepen into issues such as judicial decisions, emotions and artificial intelligence. Topics worked from connoisseurs of sciences such as law and technology that unify efforts to give rise to artificial superior knowledge. When processing large volumes of information, they emanate a sentence, which as a doctrinal vector wishes to maintain legal certainty and comply with good practices that cause acceptance and legitimacy in society.